Fatwa of MUI and Islamic Jurisprudence Council on Stem Cells from The Perspective of Qawaid Fiqhiyyah - Yasin, Yuli; Sahar, Sahar; Saepulloh, Aep; Yahyaoui, Abdelghani (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This article discusses two fatwas issued by Islamic organizations—the Indonesian Ulema Council (MUI) and the Islamic Fiqh Council—regarding stem cell therapy, with the aim of analyzing the arguments of each council, examining their legal foundations, and assessing the strength of the legal reasoning in each. Stem cell therapy is one of the newest therapeutic approaches being developed in many countries after medical research demonstrated its success in treating chronic diseases such as cancer. However, some Islamic societies do not permit such treatments unless they are officially permitted by Islamic jurists through fatwas. Regarding the use of stem cells, the ruling on their use has not been discussed by the imams of the four madhabs. Therefore, it has become among contemporary medical fiqh issues, leading to scholarly disagreement over the ruling on their use. In this study, the researchers relied on a qualitative research approach and utilized documents and secondary sources to analyze Fatwa No. 51, issued by the Indonesian Council of Ulema in 2020, and the Islamic Fiqh Council of the Muslim World League decision in 2003 during its seventeenth session regarding the use of stem cells from the perspective of qawaid fiqhiyyah “The original ruling of beneficial things is permissible.” The findings suggest that both councils differed on the original ruling on stem cell therapy, ranging from prohibition to permissibility, depending on the type of substances in which stem cells are considered. However, the permissibility of stem cell therapy serves a predominant benefit, potentially saving patients and helping combat many chronic diseases. This analytical study contributes to enhancing the contemporary jurisprudential understanding of modern medicine and advocates for changes in MUI fatwa that could significantly improve the quality of life by ensuring the use of stem cells without the condition of necessity or hajah shari’yyah.